2022
DOI: 10.1093/plphys/kiac033
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Cas-mediated transcriptional control and epi-mutagenesis

Abstract: Tools for sequence-specific DNA binding have opened the door to new approaches in investigating fundamental questions in biology and crop development. While there are several platforms to choose from, many of the recent advances in sequence-specific targeting tools are focused on developing Clustered Regularly Interspaced Short Palindromic Repeats- CRISPR Associated (CRISPR-Cas)-based systems. Using a catalytically inactive Cas protein (dCas), this system can act as a vector for different modular catalytic dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 177 publications
(259 reference statements)
0
12
0
Order By: Relevance
“…It was later shown that ZF fusions with many other RdDM-related proteins also caused FWA silencing and methylation [12][13][14] . However, it is largely unknown whether ZF fusions with non-DNA-methylation-related chromatin proteins can also trigger target gene silencing 15 .…”
Section: The Heritability Of Target Gene Silencing In Zf Fusionsmentioning
confidence: 99%
“…It was later shown that ZF fusions with many other RdDM-related proteins also caused FWA silencing and methylation [12][13][14] . However, it is largely unknown whether ZF fusions with non-DNA-methylation-related chromatin proteins can also trigger target gene silencing 15 .…”
Section: The Heritability Of Target Gene Silencing In Zf Fusionsmentioning
confidence: 99%
“…Both prokaryotes and eukaryotes have made significant use of the Cas9-CRISPR system for genome editing by extensive base pairing between the target DNA and a single guide RNA (sgRNA). The target region must also be surrounded by a short protospacer adjacent motif (PAM) sequence before the Cas9 recognizes and cleaves the target DNA ( Chen et al., 2022 ; Chen S et al., 2021 , Chen M et al., 2021 ; Hajian et al., 2019 ; Ganie et al., 2021 ; Gardiner et al., 2022 ; Gehrke et al., 2022 ). A sgRNA may cause unanticipated, off-target changes in the cell when it recognizes a non-target region that is almost identical to the target region and has few base mismatches.…”
Section: Why Crispr-cas Ge Better Than Zfns and Talens Genome Editing?mentioning
confidence: 99%
“…Such genes typically become separated during inheritance if they are dispersed throughout a chromosome, which causes the loss of a desired trait during breeding. The perfect agricultural plant has a high yield, is palatable, and is pest- and disease-resistant ( Chen M et al., 2021 , Chen S et al., 2021 ; Ganie et al., 2021 ; Gardiner et al., 2022 ; Gehrke et al., 2022 )…”
Section: What Benefits Might Crispr/cas-based Gene Editing Offermentioning
confidence: 99%
“…CRISPR/Cas was first described as an immune system of archaea and bacteria for defense against viruses by specific interaction of short-viral sequences based on complementarity ( Labrie et al, 2010 ). The system consists of an RNA sequence complementary to the target sequence known as the spacer or CRISPR RNA (crRNA), and a scaffold sequence followed by the CAS protein known as the trans-activating crRNA (tracrRNA; Deltcheva et al, 2011 ; Gardiner et al, 2022 ). The most used system is the CRISPR/Cas9 ( Figure 1 ).…”
Section: Molecular Editing Tools To Improve Plant Immunity Against Vi...mentioning
confidence: 99%